Pengaruh Parameter Pemesinan terhadap Kualitas Hasil Potong Mesin Bubut Maximat V13 pada Benda Kerja Poros PVC - Kasijanto kasijanto; Sadar Wahjudi; Listiyono Listiyono; Muhammad Fakhruddin (Jurnal Energi dan Teknologi Manufaktur, 2019)
Metal cutting process (cutting process) is to cut metal to get the shape and size and quality of the planned cutting surface. The metal cutting process is carried out with special tools, according to the type of cutting process. So the tools for one process cannot be used in another process, even for similar processes, the tools cannot be exchanged if the cutting plans are not the same. Lathe process is a machining process to produce cylindrical machine parts which are carried out using a Lathe. Its basic form can be defined as the machining process of the outer surface of cylindrical or flat lathe objects. Polyvinyl Chloride, commonly abbreviated as PVC, is the third-order thermoplastic polymer in terms of total usage in the world, after Polyethylene (PE) and Polypropylene (PP). Worldwide, more than 50% of PVC produced is used in construction. PVC is produced by polymerizing vinyl chloride monomers (CH2 = CHCl). Because 57% of its mass is chlorine, PVC is the polymer that uses the lowest petroleum feedstock among other polymers. This research follows up the selection of configuration of the lathe machining process using plastic work pieces. In this study, Maximat V13 lathe and PVC type plastic were used. The variation of machining processes are spindle rotation (320, 540, and 900 rpm), feeding speed (0.07, 0.14, and 0.28), the use of tool types (carbide and HSS) and cooling (without cooling, coolant, and oil). So, with this research, it is expected that the optimal parameters in determining the configuration of the lathe machining process on a PVC work piece to produce a good turning surface can be achieved